CONTRIBUTION PRINCIPAL LEADERSHIP, MOTIVATION AND WORK ENVIRONMENT TO THE ACHIEVEMENT OF TEACHERS OF SDN SE GUGUS ALALAK DISTRICT OF NORTH BANJARMASIN - Nathalia, Deasy; Saleh, Muhammad; Aslamiah, Aslamiah (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The purpose of this study was to describe: (1) the amount of contribution of the principal's leadership on the achievment of Public Elementary School Teachers in Alalak Cluster, North Banjarmasin Subdistrict; (2) the amount of contribution of Teacher work motivation on the work achievment of  Public Elementary School Teachers in Alalak Cluster, North Banjarmasin Subdistrict (3) the amount of contribution of the teacher?s work environment on the work achievment Public Elementary School Teachers in Alalak Cluster, North Banjarmasin Subdistrict; (4) the amount of contribution of the principals' leadership, motivation and work environment simultaneously on the work performance of Public Elementary School Teachers in Alalak Cluster, North Banjarmasin SubdistrictThe study uses a quantitative approach with descriptive and linear regression analysis. The population in this study were all elementary school teachers in the Alalak Cluster in North Banjarmasin Subdistrict. The sample used was 104 teachers. Data collection techniques used were questionnaire and observation techniques. While the data analysis technique uses statistical tests, regression analysis and F test.The results showed that: (1) Principal leadership made an effective contribution of 31,5% on teacher work achievment, (2) Work motivation provided an effective contribution of 40% on the work achievment of teachers in SDN North Banjarmasin Subdistrict , (3) Teacher's work environment made an effective contribution of 34,4%, on the work achievment of teachers in Public Elementary School in North Banjarmasin Subdistrict (4) Principal leadership, Motivation of teacher work and Teacher's work environment simultaneously contributed 50% to the work achievment of Public Elementary School Teachers in Alalak Cluster, North Banjarmasin SubdistrictIt is recommended to parties involved in the world of education such as principals, teachers, supervisors, heads of office, should always improve the quality of their work performance so that educational goals can be achieved easily.